Implementasi Cloud Based Video Conference System Menggunakan Amazon Web Service - Alde Alanda; Deni Satria (JITCE (Journal of Information Technology and Computer Engineering), 2021)
Since December 2019, the world and Indonesia have fought a major disaster, namely the Covid-19 virus pandemic. With the rapid spread or transmission of the virus, the Indonesian government decided to impose social distancing or social restrictions that impacted the education sector. Students and lecturers cannot conduct lectures face-to-face in class or laboratory, but lectures must be conducted online. For that, we need an open-source system developed by the campus in carrying out online courses. This application was developed using cloud technology and JITSI as an open-source video-conferencing application. In this study, testing of the features that exist in video conferencing and resource usage on the server is carried out. The results of feature testing on the application run as expected with several important features used for learning such as chat, share screen, recording features that can run optimally. The result tested the system resources based on the number of participants, 31 participants with an average use of 2.1GB RAM and 78 participants with an average RAM usage of 2.8GB.